Effect of Product Quality, Customer Satisfaction, Trust, and Brand Image on Repurchase Intention. Case Study: Halal Cosmetic Products - Irhamna Mandili; Amron Zarkasih; Rika Syahmewah Munthe; Erni Wahyuni (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to investigate the factors that trigger interest in repurchasing halal cosmetic products in Indonesia. Based on previous literature studies, it was found that the variables of product quality, consumer satisfaction, trust and brand image were predictors of the emergence of intention to repurchase a product by consumers. So in this study the researchers used the variables mentioned above to predict the intention to repurchase halal products. This study uses a quantitative approach with data collection methods using online questionnaires. Respondents in this study were women who had bought halal cosmetic products in the past year. The results showed that there was a positive and significant effect on the repurchase intention of halal cosmetic products. So that all hypotheses in this study are supported. This research provides insight to practitioners and marketing managers to be able to generate interest in repurchasing their products, especially in the context of halal cosmetic products in Indonesia.